1998
DOI: 10.1136/gut.43.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosplanchnic haemodynamics and renal blood flow and function in rats with liver failure

Abstract: C aminopyrine breath test).Results-Progressive liver dysfuntion was accompanied by the development of a hyperdynamic circulation, a highly significant decrease in renal blood flow and function, and an increase in intrarenal shunting 36, 42, and 48 hours after administration of D-galactosamine. The alterations in renal blood flow and function were accompanied by significant increases in portal pressure, portal venous inflow, and intrahepatic portal systemic shunting in galactosamine treated rats compared with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 29 publications
4
32
0
1
Order By: Relevance
“…This results in the inhibition of transcription (Keppler et al 1974). GalN-induced liver injury has also been linked to renal failure (Javle et al 1998). Anand et al (2002) showed that treatment of D-GalN results in renal failure manifested by the decrease in renal blood flow, creatinine clearance in renal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…This results in the inhibition of transcription (Keppler et al 1974). GalN-induced liver injury has also been linked to renal failure (Javle et al 1998). Anand et al (2002) showed that treatment of D-GalN results in renal failure manifested by the decrease in renal blood flow, creatinine clearance in renal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…They found that rats with acute liver injury caused by galactosamine showed renal dysfunction that shared some common features with that seen in patients with hepatorenal syndrome, including decreased renal arterial blood flow, decreased GFR, and increased plasma creatinine with only minor renal histological abnormalities. Javle et al 26 also observed that acute administration of galactosamine decreased renal arterial blood flow, associated with an increase in intrarenal vascular shunts. Although the acute galactosamine model shares some similarities with patients with acute liver failure, it does differ in one important aspect, namely, urine production in this model is actually increased rather than the oliguria that usually occurs in patients with acute liver and renal failure.…”
Section: Discussionmentioning
confidence: 93%
“…13 Adenosine may also be involved in activation of the hepatorenal reflex in acute liver injury. The production of intrahepatic adenosine in acute liver injury will increase because of the increase in intrahepatic shunting that decreases the effective blood supply to hepatocytes, 26 massive inflammation [23][24][25] and the decrease in the recycling of adenosine through the adenosine kinase pathway. 34 We have recently suggested that renal function is modulated by a blood-flow-dependent hepatorenal reflex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2] Further, inhibition of hepatocyte energy metabolism, with impairment of liver marker enzymes and alteration in the membrane phospholipid composition were also reported characteristics of D-GLN induced liver damage. 3 Javle and his workers 4 reported that D-GLN induced liver injury is associated with the development of renal failure. D-GLN also causes an elevation of TNFα with increased formation of reactive oxygen species (ROS) which might be circuitously a reason for cellular oxidative insult, thereby altering the antioxidant status.…”
Section: Introductionmentioning
confidence: 99%